Developing a penal abolitionist application to drug treatment drawing from insider perspectives and lived experiences - Woodall, Denise (Criminology & criminal justice, 2020)
As evidence of a failing war on drugs mounts and a deadly opioid crisis continues,U.S. drug policy is slowly changing to less punitive responses to drug use. Colla-borations between treatment programs and law enforcement gained praise frompoliticians, but concerns regarding the impact of increased surveillance and the risingculture of control call for greater focus on these governing relationships. Framedwithin an abolitionist perspective, and incorporating insights from successful modelsof decriminalization in Portugal and deinstitutionalization in Italy, our analysis ofin-depth interviews with 117 people who are actively using opioids seeks tounderstand their perspectives on treatment drawing on lived experiences. Findingsreveal a need for a paradigm shift in drug policy as well as treatment practices andincreased access to targeted social resources in the community. An application ofpenal abolition policy requires decriminalizing (or legalizing) drug use and creatingcommissions composed of community members, peers, and professionals dis-connected from the criminal justice system.